2019
DOI: 10.3389/fnana.2019.00057
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation and Dephosphorylation of Tau Protein During Synthetic Torpor

Abstract: Tau protein is of primary importance for many physiological processes in neurons, where it affects the dynamics of the microtubule system. When hyperphosphorylated (PP-Tau), Tau monomers detach from microtubules and tend to aggregate firstly in oligomers, and then in neurofibrillary tangles, as it occurs in a group of neurodegenerative disorders named thauopathies. A hypothermia-related accumulation of PP-Tau, which is quickly reversed after the return to normothermia, has been shown to occur in the brain of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
41
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(70 citation statements)
references
References 59 publications
13
41
2
Order By: Relevance
“…Therefore, exploring these outstanding mechanisms occurring naturally in heterothermic models constitutes a unique opportunity to develop efficient responses, tools and treatments to address major environmental and health concerns. Specifically, the study of these mechanisms have potential for a better understanding of (i) protective responses against metabolic disorders such as obesity or sarcopenia ( Cotton, 2016 ), (ii) the homeostasis of neuronal functions, e.g., the maintenance of hyper-phosphorylation of Tau proteins involved in resistance to neuro-degenerative diseases ( Härtig et al, 2007 ; Luppi et al, 2019 ), and (iii) the underlying mechanisms for a state of hypothermia in humans, also called “synthetic torpor,” for therapeutic goals ( Cerri, 2017 ) or space exploration ( Choukèr et al, 2019 ). In the context of the latter, the study of protective mechanisms for the torpid brain is of particular interest as well as the implications for the gaseous molecule H 2 S involved in the potential control and maintenance of metabolic depression and protective mechanisms in the torpid state.…”
Section: Metabolic Adaptations During Torpor and Hibernationmentioning
confidence: 99%
“…Therefore, exploring these outstanding mechanisms occurring naturally in heterothermic models constitutes a unique opportunity to develop efficient responses, tools and treatments to address major environmental and health concerns. Specifically, the study of these mechanisms have potential for a better understanding of (i) protective responses against metabolic disorders such as obesity or sarcopenia ( Cotton, 2016 ), (ii) the homeostasis of neuronal functions, e.g., the maintenance of hyper-phosphorylation of Tau proteins involved in resistance to neuro-degenerative diseases ( Härtig et al, 2007 ; Luppi et al, 2019 ), and (iii) the underlying mechanisms for a state of hypothermia in humans, also called “synthetic torpor,” for therapeutic goals ( Cerri, 2017 ) or space exploration ( Choukèr et al, 2019 ). In the context of the latter, the study of protective mechanisms for the torpid brain is of particular interest as well as the implications for the gaseous molecule H 2 S involved in the potential control and maintenance of metabolic depression and protective mechanisms in the torpid state.…”
Section: Metabolic Adaptations During Torpor and Hibernationmentioning
confidence: 99%
“…The animals used for the present work were the same as those used in the experiment described in Luppi et al ( 2019 ). In contrast, however, the present work is focused on the SpCo, a division of the nervous system that was not considered in our previous analysis.…”
Section: Methodsmentioning
confidence: 99%
“…To induce ST, we used a consolidated protocol (Cerri et al, 2013 ; Luppi et al, 2019 ; Tinganelli et al, 2019 ). Briefly, a microinjecting cannula was inserted into the implanted guide cannula.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a group reported that in Arctic ground squirrel, some sites were dephosphorylated in arousal animals while others remained phosphorylated, indicating a reversible phosphorylation at selective sites ( 84 ). Similarly, tau hyperphosphorylation was shown to be partially reversed in a model inducing a hypothermic torpor-like state ( 129 ). Although hypothermia could contribute to tau hyperphosphorylation during hibernation, it was clearly demonstrated that it was not sufficient and that tau phosphorylation is regulated by other mechanisms that remain to be identified.…”
Section: Section (Ii) Comparison Of the Pattern Of Tau Hyperphosphorymentioning
confidence: 99%